2019
DOI: 10.1002/adfm.201905168
|View full text |Cite
|
Sign up to set email alerts
|

Forming Covalent Crosslinks between Polymer‐Grafted Nanoparticles as a Route to Highly Filled and Mechanically Robust Nanocomposites

Abstract: Filler aggregation in polymer matrix nanocomposites leads to inhomogeneity in particle distribution and deterioration of mechanical properties. The use of polymer grafted nanoparticles (PGNPs) with polymers directly attached to the particle surfaces precludes aggregation of the filler. However, solids composed of PGNPs are mechanically weak unless the grafted chains are long enough to form entanglements between particles, and requiring long grafts limits the achievable filler density of the nanocomposite. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 72 publications
0
36
0
Order By: Relevance
“…Hardness is a measure of the resistance against deformation, such as penetration. [ 22 ] The hardness of Red P CPL was remarkably similar to that of PVdF‐HFP CPL, despite the fact that Red P CPL contained red P particles. This indicates that the mechanical property of PVdF‐HFP CPL was negligibly changed by the addition of red P particles.…”
Section: Resultsmentioning
confidence: 95%
“…Hardness is a measure of the resistance against deformation, such as penetration. [ 22 ] The hardness of Red P CPL was remarkably similar to that of PVdF‐HFP CPL, despite the fact that Red P CPL contained red P particles. This indicates that the mechanical property of PVdF‐HFP CPL was negligibly changed by the addition of red P particles.…”
Section: Resultsmentioning
confidence: 95%
“…Silica nanoparticles were prepared via the Stöber method and then immediately functionalized with (2‐bromo‐2‐methyl)propionyloxyhexyltriethoxysilane (BHE) in the same flask as reported previously. [ 31 ] Particles were purified by repeated centrifugation and kept as a stock solution in anisole.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative method for achieving high filler content while maintaining mechanical robustness is to use short polymer grafts that contain reactive groups capable of forming covalent interparticle cross‐links; previous work has demonstrated that doing so can enhance stiffness, hardness, and damage resistance in cross‐linked PGNP films, even at loadings of 40 vol% filler. [ 31 ] Similar work has demonstrated mechanical property enhancement after thermally generating cross‐links between short aliphatic capping groups. [ 32,33 ] While this covalent cross‐linking strategy is promising, these materials were processed by slow drying from solution due to the fragility of the material prior to cross‐linking, which limits the applicability of this approach to only thin films or coatings.…”
Section: Introductionmentioning
confidence: 96%
“…To circumvent the abovementioned drawbacks, polymer grafts containing end-tethered supramolecular recognition groups with precise binding behavior have been employed in regulating the superstructures of NP assemblies. 197,[201][202][203][204] When compared with hydrophobic forces, supramolecular interactions with chemically accurate stoichiometry have several key advantages: (1) the binding strength between complementary recognition group pairs can be determined using small molecules as model systems; (2) the supramolecular recognition motifs can be designed independently from the polymer component, thereby significantly increasing the modularity of the nanocomposite building blocks; (3) the versatile nature of supramolecular binding groups can introduce multi-stimuli responsiveness into the assembly.…”
Section: Ordered Nanoparticle Arrays Via Direct Assemblymentioning
confidence: 99%
“…Preliminary evidence even suggests that such structures may possess unique and tunable optical, magnetic, or mechanical properties as a function of their structural organization. 203,204 In order to further develop the potential of NCTs for forming ordered nanocomposites, it is necessary to expand their viability to a wider array of both NCT chemical compositions (i.e., different polymers, NP cores, and supramolecular recognition groups) and assembly conditions. This will allow the preparation of different model systems for ordered nanocomposites, enabling the further study of structure-property relationships and the establishment of design rules for ordered nanocomposite materials with programmable properties.…”
Section: Ordered Nanoparticle Arrays Via Direct Assemblymentioning
confidence: 99%